Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1371/journal.ppat.1008231
|View full text |Cite
|
Sign up to set email alerts
|

Modular mimicry and engagement of the Hippo pathway by Marburg virus VP40: Implications for filovirus biology and budding

Abstract: Ebola (EBOV) and Marburg (MARV) are members of the Filoviridae family, which continue to emerge and cause sporadic outbreaks of hemorrhagic fever with high mortality rates. Filoviruses utilize their VP40 matrix protein to drive virion assembly and budding, in part, by recruitment of specific WW-domain-bearing host proteins via its conserved PPxY Late (L) domain motif. Here, we screened an array of 115 mammalian, bacterially expressed and purified WW-domains using a PPxY-containing peptide from MARV VP40 (mVP40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

6
2

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 96 publications
(122 reference statements)
3
24
0
Order By: Relevance
“…Expression and purification of GST fusion protein from pGEX-ZO1-2/3 plasmid was performed as described previously [35,36]. Briefly, the plasmids were transformed into E. coli BL21(DE3) cells and single colonies were cultured in 10ml of LB media overnight with shaking at 37˚C.…”
Section: Expression and Purification Of Gst-zo1-pdz-2 Fusion Proteinmentioning
confidence: 99%
“…Expression and purification of GST fusion protein from pGEX-ZO1-2/3 plasmid was performed as described previously [35,36]. Briefly, the plasmids were transformed into E. coli BL21(DE3) cells and single colonies were cultured in 10ml of LB media overnight with shaking at 37˚C.…”
Section: Expression and Purification Of Gst-zo1-pdz-2 Fusion Proteinmentioning
confidence: 99%
“…We recently revealed a key role for endogenous Amot in positively regulating egress and spread of PPxY-containing filoviruses (32, 33). Amotp130 contains multiple PPxY motifs that mediate interactions with WW-domains of YAP, BAG3, and WWOX (negative regulators of budding), and in doing so, function as a master regulator of several physiologically relevant pathways/processes, including transcription (Hippo pathway), actin polymerization, and tight junction (TJ) formation/integrity (4554).…”
Section: Discussionmentioning
confidence: 99%
“…MARV, like many other enveloped RNA viruses, relies on its matrix protein (mVP40) to direct and promote budding of infectious virions. We and others have demonstrated that mVP40 completes the budding process, in part, by using its highly conserved PPxY L-domain motif to hijack host proteins/pathways that then facilitate efficient virus-cell separation (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). One of the best characterized host interactors is WWdomain containing E3 ubiquitin ligase, Nedd4 (7,(16)(17)(18).…”
mentioning
confidence: 99%
“…Notably, we and others have shown that Nedd4 and Nedd4 family members physically interact with viral PPxY motifs via one or more of their WWdomains, and functionally interact with viral PPxY-containing proteins to enhance or promote budding of virus-like particles (VLPs) and live virus (7,(16)(17)(18)(19)(20)(21)(22)(23)(24). The highly conserved physical and functional nature of the PPxY motif in a wide array of RNA viruses, makes it an attractive target for the development of antivirals (2,(25)(26)(27)(28)(29)(30). Indeed, compounds targeting the PPxY/WW-domain virus-host interaction would be predicted to dampen or reduce the ability of the virus to bud or pinch-off from infected cells, thus allowing an individual's immune system more time to combat and clear the virus.…”
mentioning
confidence: 99%
See 1 more Smart Citation